2017
DOI: 10.9790/1959-0601010112
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Women Regarding Vaginal Discharge

Abstract: Abstract:The present study aimed to assess women awareness regarding vaginal discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…The study at Mansoura University regarding awareness of women regarding vaginal discharge, majority of Muslim women (97.6%) had complaints of discharge. 6 While the study conducted by Guntoory et al 95% of the respondents were Hindus. 7 Most subjects in our study had completed education up to secondary level (52.3%) while the proportion of graduates were merely 4.3%.…”
Section: Resultsmentioning
confidence: 97%
“…The study at Mansoura University regarding awareness of women regarding vaginal discharge, majority of Muslim women (97.6%) had complaints of discharge. 6 While the study conducted by Guntoory et al 95% of the respondents were Hindus. 7 Most subjects in our study had completed education up to secondary level (52.3%) while the proportion of graduates were merely 4.3%.…”
Section: Resultsmentioning
confidence: 97%
“…Bro [ 25 ] found that fear of having a serious disease or a sexually transmitted disease was the reason for the visit to the general practitioner in more than half of women in Denmark. Zaher et al [ 26 ] documented that more than half of their study women did not consider VD as a serious problem that need a medical examination. A study [ 27 ] also found that most women expressed that they use home remedies before consulting a doctor for AVD.…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini sejalan dengan penelitian dilakukan di Mansoura University, Mesir pada tahun 2017 didapatkan hubungan yang signifikan antara praktik genital hygiene dengan kejadian keluhan keputihan (p= 0.044), dari 500 responden 35,8% membersihkan vagina dengan jemari dan 34,2% membersihkan hanya menggunakan air mengalir, 69,6% menggunakan pakaian dalam terbuat dari katun dan 53,6% menggantinya secara rutin, dan sebagian besar dari jumlah responden yaitu 96,2% memotong rambut kemaluan secara rutin. 15…”
Section: Hubungan Praktik Personal Hygiene Dengan Kejadian Keputihanunclassified